2022
DOI: 10.1007/s40145-022-0594-2
|View full text |Cite
|
Sign up to set email alerts
|

Equiatomic 9-cation high-entropy carbide ceramics of the IVB, VB, and VIB groups and thermodynamic analysis of the sintering process

Abstract: The preparation of high-entropy (HE) ceramics with designed composition is essential for verifying the formability models and evaluating the properties of the ceramics. However, inevitable oxygen contamination in non-oxide ceramics will result in the formation of metal oxide impurity phases remaining in the specimen or even escaping from the specimen during the sintering process, making the elemental compositions of the HE phase deviated from the designed ones. In this work, the preparation and thermodynamic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…[38][39][40] In recent years, the development of high-entropy ceramics (HECs) has provided a good opportunity for improving the performances of ZrB 2 -based ceramics by designing multicomponent solid solutions at atomic level due to high entropy effect, lattice distortion effect, sluggish diffusion, and "cocktail" effect. [41][42][43] The enhanced hardness, [44][45][46] thermal, 47,48 oxidation, [49][50][51] corrosion, 52,53 and irradiation resistance 54,55 can be found in reported high-entropy carbides, 56,57 nitrides, 58,59 borides, [60][61][62] oxides, 63,64 or silicides. 65,66 However, open reports are mainly focused on the preparation and properties of HECs with an equimolar ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] In recent years, the development of high-entropy ceramics (HECs) has provided a good opportunity for improving the performances of ZrB 2 -based ceramics by designing multicomponent solid solutions at atomic level due to high entropy effect, lattice distortion effect, sluggish diffusion, and "cocktail" effect. [41][42][43] The enhanced hardness, [44][45][46] thermal, 47,48 oxidation, [49][50][51] corrosion, 52,53 and irradiation resistance 54,55 can be found in reported high-entropy carbides, 56,57 nitrides, 58,59 borides, [60][61][62] oxides, 63,64 or silicides. 65,66 However, open reports are mainly focused on the preparation and properties of HECs with an equimolar ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, considerable interests in HEUHTCs have been triggered in the field of materials science. However, up to now, studies on the preparation and characterization of HEUHTCs are mainly focused on single-anion HEUHTCs including carbides J u s t A c c e p t e d 3 [12][13][14][15], borides [3,16,17], nitrides [18][19][20], and silicides [21][22][23][24]. Compared with the widely investigated single-anion HEUHTCs, multi-anionic HE carbonitride UHTCs have higher configuration entropy, wider performance regulation space, and better mechanical properties, which have ignited extensive attentions from researchers [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…presents the Gibbs free energy as a function of temperature for reactions (4)-(13). Based on the principle of the lowest Gibbs free energy, at 1700 ℃, ∆G˂0, metal oxides can participate in the reaction to generate the corresponding carbides and nitrides, the sequence of the possible carbides and nitrides generated are NbC, NbN, TaC, TaN, TiN, TiC, ZrN, HfN, ZrC and HfC.…”
mentioning
confidence: 99%
“…MiC and MiN whose hardness can be as high as 20 GPa are often used as superhard materials. Besides, some have the same crystal structure, such as face‐centered cubic (Fcc) and hexagonal close‐packed, which makes them mutually soluble to form solid solutions under certain conditions 1–5 . Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, some have the same crystal structure, such as face-centered cubic (Fcc) and hexagonal close-packed, which makes them mutually soluble to form solid solutions under certain conditions. [1][2][3][4][5] Refs. [6,7] have shown that Ti atoms occupy the lattice points of the Fcc crystal, and B, C, and N atoms occupy the octahedral sites.…”
Section: Introductionmentioning
confidence: 99%